Association of vascular endothelial growth factor expression with patohistological parameters of cutaneous melanoma - Gačević, Milomir; Jović, Milena; Zolotarevska, Lidija; Stanojević, Ivan; Novaković, Marijan; Miller, Karolina; Šuljagić, Vesna; Mijušković, Željko; Vojvodić, Danilo (Vojnosanitetski pregled, 2017)
Background/Aim. Melanoma is the most aggresive malignant tumor of the skin. Contradictory data was published on vascular endothelial growth factor (VGEF) in tumor samples and its role in skin melanoma progression and prognosis. The aim of this study was to investigate the significance of VEGF expression as a prognostic parameter in melanoma. Methods. The experimental group included 81 patients with primary skin melanomas treated from 2009 to 2013 at the Military Medical Academy, Belgrade. The control group included 20 patients with dysplastic and 20 with benign naevi. Stratification was done according to gender, age, clinical and patological stage, localization, histologic type, Clark’s, Breslow, mitotic count, regression and ulceration, tumor infiltrating lymphocytes and metastatic spread. Immunohistochemical staining was performed on skin biopsies using DAKO anti-VEGF antibodies (Ab), LSABTM +HRP, DAB and microvawe antigen (Ag) retrieval in DAKO pH 9.0 solution. For statistical data analysis was done with ANOVA, Bonferroni, Mann Whitney and Wilcoxon test. Results. The mean intensity of VEGF staining was statistically significantly higher in melanomas than in benign or dysplastic naevi. Furthermore, the highest recorded values were in Ia and IV clinical stages. The majority of melanomas with high intensity of VEGF staining were in pT1a pathological stage. Melanomas with the highest mitotic count (> 6) had a significantly higher intensity of VEGF staining than those with < 2 mitoses. The higest intensity of staining was in melanomas without significant lymphocytic infiltrate and the lowest was in those with brisk lymphocytic infiltrate, thus a statistical difference was siginifant. The mean intensity of VEGF staining was highest in melanomas with lymphovascular invasion. There was no statistically significant difference between VEGF and any other parameter. Conclusion. VEGF in primary skin melanomas plays an important role in tumor progression and is linked to the absence if tumor infiltrating lymphocytes and the presence of lymphovascular invasion. More detailed studies have to be done on VEGF prognostic value in melanoma on a larger number of patients.
Keywords: melanoma; skin; vascular endothelial growth factors; histology; immunohistochemistry; sensitivity and specificity